Case Reports: A role of postoperative radiation therapy in completely resected early stage intrathyroid thymic carcinoma: a case report and literature review of the diagnosis and treatment - Cui, Ailin; Du, Yaoqiang; Hou, Chunjie; Zhang, Lin; Sun, Litao; He, Hongfeng (Frontiers in Oncology, 2023)
Background: Intrathyroid thymic carcinoma (ITTC) is a rare malignant tumor of the thyroid, probably arising from ectopic thymus or branchial pouch remnants. Most of the literature recommended radical resection as the fundamental treatment for ITTC, and postoperative radiation appears to be able to reduce the recurrence rate in patients with advanced ITTC. However, the issue of adjuvant radiotherapy in completely resected early-stage ITTC has been controversial. Case presentation: Here, we reported a new case of early-stage ITTC that treated with total thyroidectomy and the right central neck dissection. Postoperative external beam radiation therapy (50.0 Gy/25 fractions) was given to the thyroid bed and bilateral cervical lymph node area since the tumor involved part of the sternal thyroid muscle. At 4-year follow-up after completion of radiotherapy, she is without evidence of locally recurrent or distant disease. Conclusion: Since there are no current guidelines for early-stage ITTC, in combination with this case and previous literature, we may suggest routine adjuvant radiotherapy should be considered in patients with incompletely resected tumors and extraparenchymal extension of ITTC. Moreover, we summarized comprehensive and advanced diagnosis, treatment, prognosis of ITTC and comparison between ITTC, primary squamous cell carcinoma of thyroid gland, differentiated thyroid cancer, and anaplastic thyroid cancer.